Adaptation and psychometric study of two instruments of couple: index of marital satisfaction and marital instability scale - Iraurgi, Ioseba (2009)
This study examines the psychometric characteristics of the instruments of partner: Index of Marital Satisfaction - IMS (Booth and Edwards, 1983) and Marital Instability Scale - EIM (Hudson, 1992). Both instruments are applicable to situations of family crisis and have proved effective in predicting divorce or separation. We used a sample consisting of 183 women. It highlights the strong psychometric properties of both scales, with high reliability coefficients (alphas 0.90 and 0.97 for the ISM and EIA, respectively), correct structural validity (validated by confirmatory factor analysis), and adequate concurrent validity (correlation coefficients above 0.40 in related constructs). All this allows adaptation of both spanish valuation couple as useful for their application. It argues, however, the need to test their goodness metrics in different samples, contexts and clinical problems of couples.